Essay on the Solution of Justice Problems in Colombia - (:unkn) unknown (My University, 2016)
Justice is an essential service that should be provided efficiently in all parts of the country. To develop within a society, each individual and family requires timely access to the administration of justice in all areas of law—civil, labor, family and criminal justice. The public good of justice goes beyond democracy, and is an integral component in the definition of any society.